OVERVIEW OF VULNERABILITIES IN SMART CONTRACTS WRITTEN IN SOLIDITY - Peschanenko, Volodymyr; Rud, Viktor (Journal of Information Technologies in Education (ITE), 2024)
The increasing interest in blockchain and smart contract technologies has brought attention to the security challenges associated with these innovative solutions. Smart contracts, which are written in the Solidity programming language and executed on the Ethereum platform, offer new opportunities for automating legal and financial transactions. However, they also pose risks related to code and data security. The article discusses the fundamental principles of smart contracts, with a focus on the Solidity language and the vulnerabilities that commonly arise during development. The authors provide a concise overview of academic research on smart-contract security, highlighting the significance of each paper. This review provides readers with an understanding of the current state of research in smart contract cybersecurity and emphasizes the importance of enhancing the security of blockchain technologies. Given the increasing complexity and expanding applications of blockchain technologies, studying smart contract vulnerabilities is crucial. This study highlights the significance of conducting a systematic analysis of cyberattacks, including a detailed examination of each type and incident of attack. This approach can prevent potential vulnerabilities and effectively minimize the risks of attacks. Such an approach is crucial to ensure the further development and popularization of blockchain technology. The paper provides examples that illustrate real-life cases of smart contract vulnerabilities and discusses the consequences of such vulnerabilities. Analyzing these examples provides insight into the importance of careful code development and auditing, as well as the significance of ongoing cybersecurity education and training for developers. Recommendations for future research are provided and vectors for future work are outlined. This paper may interest individuals involved in smart contract development, blockchain and cybersecurity research, and those interested in blockchain technology.